PENGARUH METODE PEMBUATAN TERHADAP SIFAT FISIS TABLET KURKUMIN DAN ANALOGNYA - -, Sugijanto L (STIKES Muhammadiyah Klaten, 2009)
ABSTRACT: The effect of fabrication on physical properties of cur cumin tablets have been investigated. The cur cumin tablet were prepared by direct compression and granulation methods. The tablets obtained were determined their physical properties including the hardness, disintegration time, friability, weight and content uniformity. The result showed that all of physical properties of cur cumin tablets fulfill the official requirements. There are differences on the hardness, disintegration time and content uniformity between cur cumin tablets were prepared by direct compression and granulation method significantly (P<0,05). Key-words : Curcumin, granulation, direct compression, physical properties of tablet.